2012
DOI: 10.4088/jcp.11m07552
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, Abdominal Obesity, and Onset of Depression in Older Men and Women

Abstract: Objective The mechanisms that underlie the association between abdominal obesity and depression risk in older persons are not well known, but the “leptin hypothesis” of depression suggests that leptin resistance may be involved in mood regulation. We tested whether high circulatory concentration of leptin, alone and in combination with visceral adiposity, is associated with onset of depression in a sample of older persons. Method Participants were 1220 men and 1282 women aged 70–79 years, enrolled in the Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 44 publications
8
56
3
1
Order By: Relevance
“…Proinflammatory cytokines such as interleukin-6 and C-reactive protein have been shown to predict future cardiovascular events (Cesari et al, 2003;Pearson et al, 2003;Ridker et al, 2000), and have also been linked to depressive symptoms in cross-sectional (Goldbacher & Matthews, 2007;Howren et al, 2009;Mossner et al, 2007) and prospective designs (Stewart et al, 2009). More recently, leptin has been shown to be a key marker of depression and a potential mechanistic link in its relationship to cardiovascular disease (Chirinos, Goldberg, et al 2013;Chirinos, Morey-Vargas, et al 2013;Labad et al, 2012;Milaneschi et al, 2012;Morris et al, 2012). Other candidate biological pathways in this relationship include sympathetic activation (Carney et al, 2000;Kawachi et al, 1995), pro-coagulant factors (Strike & Steptoe, 2004) and endothelial dysfunction (Ghiadoni et al, 2000;Narita et al, 2007;Pitsavos et al, 2006;Yasunari et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines such as interleukin-6 and C-reactive protein have been shown to predict future cardiovascular events (Cesari et al, 2003;Pearson et al, 2003;Ridker et al, 2000), and have also been linked to depressive symptoms in cross-sectional (Goldbacher & Matthews, 2007;Howren et al, 2009;Mossner et al, 2007) and prospective designs (Stewart et al, 2009). More recently, leptin has been shown to be a key marker of depression and a potential mechanistic link in its relationship to cardiovascular disease (Chirinos, Goldberg, et al 2013;Chirinos, Morey-Vargas, et al 2013;Labad et al, 2012;Milaneschi et al, 2012;Morris et al, 2012). Other candidate biological pathways in this relationship include sympathetic activation (Carney et al, 2000;Kawachi et al, 1995), pro-coagulant factors (Strike & Steptoe, 2004) and endothelial dysfunction (Ghiadoni et al, 2000;Narita et al, 2007;Pitsavos et al, 2006;Yasunari et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a crosssectional study by Pasco et al [47] , demonstrated that depressive disorders can be predicted by high serum leptin levels among female nonsmokers. In addition, elevated leptin levels as well as visceral fat seem to predict depressive symptoms in old men [48] . Likewise, in a longitudinal study by Milaneschi et al [49] high levels of leptin and abdominal adiposity were a high risk factor for the development of depressed mood over a 9year follow up.…”
Section: Leptin's Role In Mood Regulationmentioning
confidence: 99%
“…Furthermore the use of psychotropic medications, often prescribed for depressive and anxiety disorders, might be an additional explanatory risk factor for weight change (Virk et al, 2004;Demyttenaere and Jaspers, 2008;Vieweg et al, 2008;Hasnain and Vieweg, 2013). Underlying shared biological abnormalities such as inflammation, leptin or HPA-axis dysregulations could further play a linking role between mental health and weight change (Bjorntorp, 2001;Bornstein et al, 2006;Pasco et al, 2008;Vreeburg et al, 2009;Milaneschi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%